Effectiveness of weight management, smoking cessation and alcohol reduction interventions in changing behaviors during pregnancy: an umbrella review protocol. (October 2016) - Dinsdale, Sarah; Azevedo, Liane Beretta; Shucksmith, Janet; Newham, James; Ells, Louisa Jane; Jones, Dan; Heslehurst, Nicola
Abstract : Review objective/question: The objective of this umbrella review is to examine the effectiveness of different types of weight management, smoking cessation and alcohol reduction interventions in producing explicitly measured behavior change or proxy measures of behavior change in pregnant women. Specifically the review question is: are weight management, smoking cessation and alcohol reduction interventions effective in producing behavior change in pregnant women?